A COMPARITIVE STUDY ON HYPER AND HYPOTHYROIDISM CONDITIONS IN NELLORE DISTRICT WOMEN - G. SUJATHA; S. HASEENABHANU; S. K. RUXANABEGUM; K.THYAGARAJU (The Bioscan, 2010)
A Comparative study on hyperthyroidism and hypothyroidism in female employees of south coastal area of Nellore was made. The females of the age 60 and above were prone for hyperthyroidism and hypothyroidism.500 female employees blood was collected from the south coastal area, Nellore, for the determination of hyper and hypothyroidisms by using the method micro plate enzyme immuno assays (EIA). The coastal area females’ serum analysis has revealed 9% of prone for hyperthyroidism and 10% for hypothyroidism. Overall 25% of all females with a sex ratio of 5:1 most often, in between the ages 20and 60 years, were affected with hyperthyroidism. Estimation of serum T3, T4, TSH, is necessary for the diagnosis of thyroid disorders. For better results, supplementation of iodine to salt may help hypothyroidic patients to recover normally. Whereas surgery maybe necessary for hyperthyroidism.